MECHANICAL AND VISCOELASTIC PROPERTIES OF COCONUT COIR FIBRE REINFORCED HIGH-DENSITY POLYETHYLENE COMPOSITE FOR APPLICATION AS WALL TILE - Babatunde, O. A.; Omale, P. E.; Iorver, Precious D. (FUDMA JOURNAL OF SCIENCES, 2025)
In the effort to clean up the environment and transform plastic waste into valuable resources, the mechanical and thermal properties of a composite made from High- Density Polyethylene (HDPE) and Coconut Coir Fiber (CCF) were examined to determine the optimal blending ratio for producing wall tiles. The Coconut Coir Fiber was treated with 10% w/v sodium hydroxide and mixed with waste HDPE using a roll melt mixing compression molding technique. The study assessed tensile strength, flexural strength, and hardness. While the addition of coconut coir fiber improved the hardness of recycled HDPE, it did not enhance flexural or tensile strengths. The viscoelastic properties, evaluated using a 242E dynamic mechanical analyzer over a temperature range of 30°C to 130°C at frequencies of 2 Hz, 5 Hz, and 10 Hz, revealed that the composite exhibited better thermal stability at higher temperatures than waste HDPE.